+0  
 
0
273
2
avatar

2x -( y+2)/2 = 22

3x + (y+2)/3 = 7

Solve the set by substitution method

Guest May 27, 2015

Best Answer 

 #2
avatar+248 
+15

It'd be easier to multiply the first equation by 3 and the second by 2 then subtract the 2nd equation from the 1st to get one equation in terms of y, but since you said it had to be the substitution method here goes:

$$2x-\frac{y+2}{2} = 22 \\ 2x = 22+\frac{y+2}{2} \\ x=11+\frac{y+2}{4}$$

Now Substituting x into the other Equation:

$$3[11+\frac{y+2}{4}] + \frac{y+2}{3} = 7 \\ 99+\frac{9(y+2)}{4}+y+2 = 21 \\ 396+9y+18+4y+8=84\\13y=-338\\y=-26\\x=11+\frac{-26+2}{4}\\
x=5$$

Brodudedoodebrodude  May 27, 2015
Sort: 

2+0 Answers

 #1
avatar+26322 
+15

Rearrange the first equation to get x = (y+2)/4 + 11

 

Put this into the second equation

3*(y+2)/4 + 3*11 + (y+2)/3 = 7

 

Multiply through by 4*3

9*(y+2) +12*3*11 + 4*(y+2) = 12*7

So

9y + 18 + 396 + 4y + 8 = 84

13y + 422 = 84

13y = -338

y = -26

 

Put this back into the first equation above

x = (-26+2)/4 + 11

x = 5

 

You should check these by putting them back into the original equations.

.

Alan  May 27, 2015
 #2
avatar+248 
+15
Best Answer

It'd be easier to multiply the first equation by 3 and the second by 2 then subtract the 2nd equation from the 1st to get one equation in terms of y, but since you said it had to be the substitution method here goes:

$$2x-\frac{y+2}{2} = 22 \\ 2x = 22+\frac{y+2}{2} \\ x=11+\frac{y+2}{4}$$

Now Substituting x into the other Equation:

$$3[11+\frac{y+2}{4}] + \frac{y+2}{3} = 7 \\ 99+\frac{9(y+2)}{4}+y+2 = 21 \\ 396+9y+18+4y+8=84\\13y=-338\\y=-26\\x=11+\frac{-26+2}{4}\\
x=5$$

Brodudedoodebrodude  May 27, 2015

27 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details